Assessing the factorial structure of the mental illness public stigma in Spain. Issue 18 (28th August 2021) - Saavedra, Javier; Arias-Sánchez, Samuel; Corrigan, Patrick; López, Marcelino
Abstract: Purpose: Despite the importance of the stigma construct for the rehabilitation of people with severe mental illness, there are still no scales that offer a measurement for public stigma in Spanish with good psychometric properties. The aim of this paper is to refine and improve an existing scale to measure public stigma towards people with severe mental illness among the Spanish population. We also intended to decrease the number of items in order to facilitate its applicability. Method: 402 college students (73% women) responded to the attributional questionnaire (AQ27) in two subsamples. Exploratory and confirmatory factorial analysis with high cutoffs were conducted. The convergent validity with the resource allocation questionnaire was also tested. Results: We have obtained a parsimonious tool, with 14 items and four factors, and some reliable psychometric indexes and convergent validity. The factors obtained were dangerousness-fear, lack of solidarity, coercion and avoidance. Conclusions: These results improve the findings from other studies that try to validate the AQ27 in other languages. We discuss the different factors that should be considered in the estimation of public stigma and the necessity to implement programmes to reduce it to enable recovery. IMPLICATIONS FOR REHABILITATION: Since the public stigma of mental illness is an obstacle to recovery and rehabilitation, reliable instruments are needed to assess it. A parsimonious instrument in Spanish with good psychometric characteristics for measuring public stigma is obtained. Using exploratory and confirmatory factor analysis, a questionnaire of 14 items is obtained. Four factors constitute the instrument: "dangerousness-fear", "coercion", "lack of solidarity", and "avoidance".